PENGEMBANGAN MEDIA DIORAMA PADA PEMBELAJARAN TEMATIK TEMA 3 PEDULI TERHADAP MAKHLUK HIDUP UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SD NEGERI MARINDAL 104211 KEC. MEDAN AMPLAS - Tenti Armisah Gajah; Dara Fitrah Dwi (STKIP Subang, 2023)
This research aims to find out how to develop diorama media in thematic learning on the theme of caring for living creatures in class IV and efforts to improve student learning outcomes in class IV at Elementary School 104211 Marindal. This research is a type of research and development using the ADDIE model, namely analysis, design, development, implementation and evaluation. The subject of this research is diorama media on the theme (caring for living creatures) and the object of this research is learning material on the theme (caring for living creatures) to improve the learning outcomes of fourth grade elementary school students. Quantitative data is obtained from the formula used to determine the suitability of media and materials. The data obtained is used as a reference for making revisions to the products being developed. Based on the calculations above, the results of the overall assessment of the material experts reached the instrument used to collect data, namely a questionnaire. The results of media validation for the theme learning diorama (caring for living creatures) were media expert validation obtained 82% with the criteria being very suitable for use and suitable for development in learning the themes of caring for living creatures sub theme 1 very feasible, material expert validation obtained a score of 80% with the criteria are suitable for use, the teacher's response received a score of 97% with the criteria very suitable for use and the student response received a score of 95% with the criteria very suitable for use. Based on the data obtained, it can be concluded that diorama media can improve learning outcomes for fourth grade elementary school students. Can improve the learning outcomes of class IV students